The effects of vitamin C supplementation on oxidative and immune response and post exercises inflammation: Vitamin C in health and physical performance - critical review - Durzyńska, Aleksandra; Gutowski, Patryk; Drozdowska, Katarzyna; Żołądkiewicz, Katarzyna; Słojkowska, Agnieszka (Journal of Education, Health and Sport, 2025)
Ascorbic acid, also called vitamin C is the one of the exogenous vitamins, functioning in human body as ascorbate and affecting many body systems. In presented revive we try to show most of the well-known, and importance proprieties of this compound focusing mainly on its role in health and physical activity. Interaction of this antioxidant with many other compounds and body tissues revels its free radicals scavenging properties and the main possible role in body functioning. However, the benefits of using this vitamin are still controversial and the presented properties, like those of many other antioxidants, are questioned. On the other had high safety of use and vilely known properties sill indicate that this vitamin may have potential use in sport and health. In presented work we tried to focus mainly on the properties of this vitamin in context of exercise depended demands and how high vitamin C consumption affects general health of different population and how it can be useful type of supplementation in physical activity.